IDENTIFIKASI Taenia solium PADA FESES WARGA DESA KARANG LANGIT DENGAN KEBIASAAN KONSUMSI DAGING BABI - Nurmansyah, Dian; Maramis, Javercintya Angelica; Puspawati, Puspawati Puspawati (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2023)
Taenia solium is a parasite class of cestode lives in the small intestine of humans to get the nutrition of its life. Humans are definitive host and intermediate host is pigs. Taenia solium infection is often found in areas where a lot consumed of raw or undercooked pork that contains cysticercus, or in areas with poor sanitation. If humans ingest proglottid or Taenia solium eggs, cysticercus cellulose larvae can grow in the host. This research was conducted of Karang Langit village on March 2021, the type of research used was survey descriptive with a cross sectional research design. The aim of this study to aware the presence of Taenia solium infection in the feces of the village. The research method used is native method. Based on the results of the research, no progglotid were found, nevertheless was found eggs of Taenia solium by 2,25%